Foreign direct investment and cost uncertainty: Correlation and learning effects - Anthony Creane; Kaz Miyagiwa (Osaka University, Institute of Social and Economic Research (ISER), 2007)
We examine a foreign firm's choice between exporting and foreign direct investment (FDI) under country-specific cost uncertainty. Unlike exporting, FDI exposes foreign and home firms to common shocks. This results in a correlation of strategies, harming the firms. However, the exposure to common shocks also benefits the firms by enabling them to learn each other's cost realization. The net effect is negative, implying that country-specific cost uncertainty forms a barrier to FDI. The foreign firm, then, chooses exporting unless FDI gives it a substantial cost advantage. Therefore, when FDI actually occurs, the home firm is hurt but consumers always benefit.
Keywords: D83; F12; 330; information; FDI; access mode selection; cost uncertainty; globalization; Internationale Geschäftsbeziehungen; Export; Auslandsinvestition; Strategisches Management; Kostenanalyse; Theorie